Apparatus for Strengthening Soft Water-Saturated Soils by Freezing under Engineering Objects and Structures in Cold Regions. (2017) - Moiseev, V.I.; Vasiliev, N.K.; Komarova, T.A.; Komarova, O.A.
Abstract: The paper is devoted to the construction of various earth and engineering structures being operated on soft soils in the northern regions of Russia with a pronounced continental climate and a lot of wetlands. The problem of year-round cooling of water-saturated soil to freezing temperatures in order to convert it into a frozen state of permafrost is considered. To convert the soil into a frozen state of permafrost and keep the state all year around, including the summer period, the new soil cooling apparatus has been developed. The apparatus is economical; it has no moving parts and can operate for a long time without involving any staff.